Methods for the analysis of azo dyes employed in food industry – A review - Yamjala, Karthik; Nainar, Meyyanathan Subramania; Ramisetti, Nageswara Rao (Food chemistry, 2016)
•Methods for the analysis of azo dyes for coloring food have been reviewed in detail.•We discussed extractions of azo dyes from various food matrices.•This review is mainly useful for the researchers and in food industries as a quality control tool. A wide variety of azo dyes are generally added for coloring food products not only to make them visually aesthetic but also to reinstate the original appearance lost during the production process. However, many countries in the world have banned the use of most of the azo dyes in food and their usage is highly regulated by domestic and export food supplies. The regulatory authorities and food analysts adopt highly sensitive and selective analytical methods for monitoring as well as assuring the quality and safety of food products. The present manuscript presents a comprehensive review of various analytical techniques used in the analysis of azo dyes employed in food industries of different parts of the world. A brief description on the use of different extraction methods such as liquid–liquid, solid phase and membrane extraction has also been presented.